2019
DOI: 10.35238/sufefd.549896
|View full text |Cite
|
Sign up to set email alerts
|

Evaluations of the Aphid Species Determined in Adıyaman, Malatya and Şanlıurfa Provinces for Contribution to Turkey Aphid Fauna

Abstract: Ülkemizin Doğu Anadolu bölgesinden bulunan Malatya ve Güney Doğu Anadolu bölgesinde yer alan Adıyaman ve Şanlıurfa illerinin afit faunasının belirlenmesini amaçlayan çalışma kapsamında 2015-2018 yılları arasında gerçekleştirilen örneklemelerle çalışma alanından 222 afit türü belirlenmiştir. Bu türlerden 45 tanesinin Türkiye afit faunası için yeni kayıt olduğu, ülkemiz afit faunasına yaklaşık %9 oranında katkıda bulunulduğu ve Türkiye faunasının tür sayısının bu kayıtlarla 550’e yükseldiği belirlenmiştir. Örnek… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
0
4
0
1
Order By: Relevance
“…It was clearly realized that each region and even each locality has their own aphid composition and therefore there are plausible differences in regional aphid fauna. It has been shown that there were about 85 different species determined among 3 searched areas (Görür et al, 2019). In addition to natural characteristics, recent establishment of South Eastern Dam (GAP) has caused changes in climatic, floristic, agricultural composition of South Eastern part of Turkey.…”
Section: Resultsmentioning
confidence: 99%
“…It was clearly realized that each region and even each locality has their own aphid composition and therefore there are plausible differences in regional aphid fauna. It has been shown that there were about 85 different species determined among 3 searched areas (Görür et al, 2019). In addition to natural characteristics, recent establishment of South Eastern Dam (GAP) has caused changes in climatic, floristic, agricultural composition of South Eastern part of Turkey.…”
Section: Resultsmentioning
confidence: 99%
“…In spite of a remarkable number of study was conducted during last 20 years, there are still poorly investigated areas waiting for to be studied. With these studies, considerable number of aphid species have been added Turkey aphid fauna, and some new host plant associations have also been detected (Görür, Zeybekoğlu, Akyürek, Işık, & Akyıldırım, 2009;Görür, Şenol, Akyıldırım, & Demirtaş, 2014;Görür, Şenol, Gezici, & Parmaksız, 2018;Kök & Özdemir, 2021;Şenol, Görür, Başer, & Akyıldırım Beğen, 2021;Patlar, Oğuzoğlu, Avcı, & Şenol, 2021;Kök & Kasap, 2022). Despite the recent additions, there was an interesting result that total aphid fauna of Turkey was sampled on only about 1100 plant species while there are more than12.000 plant species with a 31% endemism ratio (Görür, Şenol, Akyıldırım Beğen, & Akyürek, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Kök, Kasap & Özdemir (2016) and Kök & Kasap (2019) added 2 aphid species and the number reached to 534. Görür, Şenol & Akyıldırım Beğen (2019) listed 40 new aphid records to the aphidofauna. Recent reanalysis of the aphid species and determined host plants clearly showed that the number of the aphid taxa in Turkey reached more than 570 (Görür Şenol & Akyıldırım Beğen, 2019;Görür, Şenol, Akyıldırım Beğen & Akyürek, 2020).…”
Section: Introductionmentioning
confidence: 99%